THE ROLE OF EMPLOYEE ACHIEVEMENT: WORK ABILITY AND MOTIVATION - Zulaspan Tupti; Dinda Lestari (International Journal of Economic, Technology and Social Sciences (Injects), 2021)
The purpose of the study was to determine the effect of ability and motivation on employee performance at PT. Kimia Farma (Persero) Tbk Medan Red Cross Branch. The sample in this study were 40 respondents who were employees of PT. Kimia Farma (Persero) Tbk Medan Red Cross Branch. The results of this study were collected through a questionnaire which was processed and analyzed using Multiple Regression. The sampling method in this study used the saturated sampling method. The data quality test used is a validity test using Corrected Item Total and a reliability test using Cronbach Alpha. To test the hypothesis in this study. The data analysis technique in this study is the classical assumption test, multiple linear regression test, hypothesis testing consisting of t test, and F test and perform a determination test. That there is a positive effect of the ability variable on the employee's work performance variable, there is a positive influence of the motivational variable on the employee's work performance variable for ability and motivation to have a significant influence on the work performance of PT Kimia Farma (Persero) Tbk Medan Red Cross Branch.